Implementasi Kurikulum Berbasis Cinta Dalam Membangun Karakter Siswa DI MTs Laboratorium UIN Bukittinggi - Abdullah, Eramli Jantan (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This study aims to explore the implementation of a Love-Based Curriculum in building student character at MTs Laboratorium UIN Bukittinggi. The research employs a qualitative methodology, utilizing case study and observational approaches to gather data from teachers, students, and school administrators. Data collection methods include interviews, classroom observations, and document analysis. The findings reveal that the Love-Based Curriculum positively impacts students’ emotional and social development by fostering a nurturing environment where values such as empathy, respect, and kindness are embedded in daily activities. Students displayed enhanced emotional intelligence, interpersonal skills, and a stronger sense of belonging within the school community. However, challenges such as insufficient teacher preparation, training, and resource limitations were also identified. The study concludes that while the Love-Based Curriculum has the potential to foster character development, its success depends on continuous support and collaboration among educators, students, and the school administration. This research contributes to the academic field by linking love-based pedagogical approaches with character education, particularly in the madrasah context. It provides valuable insights for educators aiming to implement similar curricula to promote emotional and social competencies in students. Furthermore, the study emphasizes the need for a comprehensive, well-supported approach to effectively integrate values of love and empathy in educational practices, offering a model for other institutions seeking to enhance character education.